Novel Phytochemical Inhibitors of Leptin: A Molecular Docking Approach for Potential Cardiovascular and Antidiabetic Therapies - Abdul Rauf; Sumayya Qazi; Bashir Ahmad Malik; Sehar Aslam; Urooj Anwar; Usman Ali Ashfaq; Rashid Bhatti (Journal of Liaquat University of Medical & Health Sciences, 2025)
OBJECTIVE: To identify phytochemicals as potential leptin inhibitors, particularly in the context of immune and cardiovascular health, using molecular docking analysis. METHODOLOGY: This study was conducted from 2023 to 2024 with the joint efforts of the Department of Bioinformatics and Biotechnology, Government College University Faisalabad, and the Center of Excellence and Molecular Biology, University of Punjab Lahore. The 3D structure of Leptin was retrieved from the Protein Data Bank and refined for docking analyses using PyRx. A ligand library consisting of 5,006 phytochemicals was prepared from various databases. The interactions were visualized using Discovery Studio. Compounds with high docking scores were further analyzed for their ADMET properties, based on Lipinski's Rule of Five, to ensure their drug-like characteristics and predict their safety profiles. RESULTS: The compounds Peonidin, Diosmin, 7-[3-(3-hydroxy oct-1-enyl)-4,6-dioxabicyclo[3.1.1]heptan-2-yl]hept-5-exonic acid, Carnitine, Dihydrodaidzin, 4-dimethylpodophyllotoxin, 4-demethyldeoxypodophyllotoxin, (+)-sophorol and Tylophorinidine demonstrated successful binding to the Leptin. Thus, it potentially interferes with the leptin-leptin receptor interaction. Diosmin and Dihydrodaidzin showed the most vital binding score of -7.9 Kcal/mol of all the top-ranking compounds. CONCLUSION: These compounds may act as effective inhibitors of Leptin, which may help develop natural, affordable therapies for cardiovascular disorders and diabetes. However, further research is required to validate their efficacy and safety.